HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU MEROKOK SISWA SMAN 3 KOTA PAGAR ALAM - Dwi putri Sulistiya Ningsih; Dirhan Dirhan; Gemala Refoliza (Dian Nuswantoro Semarang, 2022)
Smoking behavior is considered very detrimental and has shifted to pleasant behavior, especially among schools, one of which is at the high school level. This makes students smoke in schools more. This study aims to study the relationship between knowledge and attitudes toward smoking behavior among SMAN 3 Pagar Alam students. This type of research uses a cross-sectional design to determine the sample size. The determination of the sample size using Proportional Random Sampling is as many as 64, as the sample of this study, data collection techniques using primary and secondary data, and data analysis methods using Univariate and Bivariate analysis with the Chi-Square test to determine the closeness of the relationship seen from the value of the Contingency Coefficient (C). The results showed that out of 64 students, 46.9% had less knowledge, 15.6% had sufficient knowledge, and 37.5% had good knowledge. While the relationship between attitudes and smoking behavior of students is 36 students who support and 28 students who do not support smoking behavior. There is a significant relationship between knowledge and student behavior with a value of p <0.05 (0.000) with a Contingency Coefficient (C) value category of 0.601 (strong relationship category). There is a significant relationship between the attitudes and smoking behavior of students with a p value of 0.05 (0.000) and a Contingency Coefficient (C) value of 0.672 (strong relationship category).Keywords: Knowledge, Attitude, Student Smoking Behavior.